Efficacy Of Vocal Cord Medialization by Injection Thyroplasty Using Liquid Paraffin In Relieving Hoarseness Of Voice In Idiopathic And Traumatic Unilateral Vocal Cord Paralysis - Muhammad Saleem; Muhammad Sarim Khan; Ashar Alamgir; Muhammad Hamza Rana; Hafiz Sajjad Hyder; Syeda Jamila Ali (Journal of Rawalpindi Medical College)
Objective: The objective of the study was to measure the efficacy of injection thyroplasty by liquid paraffin in the medialization of vocal cords in permanent post-traumatic or idiopathic hoarseness.